Choroidal granuloma caused by Mycobacterium Fortuitum - João Pinto da Silva Neto; Kyra Nhayanna Coutinho Machado; Luiz Roisman (International Journal of Retina and Vitreous, 2019)
Abstract Background To report a case of a chronic steroid user male patient who developed local abscesses caused by M. fortuitum and concomitant asymptomatic choroidal granuloma. Case presentation A 37-year-old african-american male with history of use of anabolic drugs and intramuscular mineral oil injections in the upper and lower limbs for 15 years for muscular hypertrophy. He developed intramuscular abscesses with systemic infection, sub-retinal lesions in both eyes and alterations in cerebrospinal fluid suggestive of mycobacteria. Considering these findings, empirical treatment for tuberculosis was started, without success. After several negative cultures of the material drained from the abscesses, finally one of the cultures isolated the agent Mycobacterium Fortuitum. Proper treatment for atypical mycobacteria was initiated with clinical and laboratory improvement. After 6 months the sub-retinal lesions regressed. Conclusions A typical choroidal granuloma caused by M. Fortuitum is a rare presentation of the infection and our report showed a good outcome with proper treatment.